2003
DOI: 10.1074/jbc.m211769200
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of 1,3-Bisphosphoglycerate Analogs Bound to Phosphoglycerate Kinase

Abstract: We have previously reported dissociation constants for a range of bisphosphonate analogs of 1,3-bisphospho-D-glyceric acid binding to yeast phosphoglycerate kinase. Data for the unsymmetrical analogs were difficult to interpret because it was not clear in which of the two possible orientations these ligands bound. Here we report a novel NMR method for quantifying orientation preference based on relaxation effects induced by titration with CrADP, which is applied to these ligands. It is shown that all ligands c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Phosphonates are structural mimics of phosphates that have found utility in probing a diverse array of biological processes including the development of clinical antiretroviral and osteoporosis drugs. 1,2 The replacement of a labile phosphate linkage with a hydrolytically more stable phosphonate 3 has facilitated the study of a variety of enzymes catalyzing phosphate bond cleavage [4][5][6][7][8] including enzymes where a transient cleavage of the phosphate occurs during catalysis. 9 Phosphonates have also been developed as inhibitors of ester hydrolysis 10,11 or as reagents for proteomic profiling of serine proteases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphonates are structural mimics of phosphates that have found utility in probing a diverse array of biological processes including the development of clinical antiretroviral and osteoporosis drugs. 1,2 The replacement of a labile phosphate linkage with a hydrolytically more stable phosphonate 3 has facilitated the study of a variety of enzymes catalyzing phosphate bond cleavage [4][5][6][7][8] including enzymes where a transient cleavage of the phosphate occurs during catalysis. 9 Phosphonates have also been developed as inhibitors of ester hydrolysis 10,11 or as reagents for proteomic profiling of serine proteases.…”
mentioning
confidence: 99%
“…First, the phosphonate 4 has a lower turnover efficiency in comparison to 1, and second, the phosphonate 5 has a higher turnover efficiency, relative to 6. It is interesting that a stereochemical change at C4, distant from the reactive site, can partially be countered by modification of the phosphate moiety (5). Potentially, the change in stereochemistry at C4 may perturb the trajectory of the phosphate, and replacing the anomeric oxygen with a methylene unit may partially realign the nucleophile trajectory as a result of the differences in geometry of the phosphonate.…”
mentioning
confidence: 99%
“…During several years the main application of the chemical shift perturbation due to paramagnetic metal ions was used to simplify 1 H NMR spectra and now the range of application is continually growing. Recently, these paramagnetic probes have been used as a tool in the refinement of macromolecular structures [78,[83][84][85][86][87], in the structure determination of the family of intrinsically unstructured proteins (IUPs) [88], medium-resolution structures for proteins in the 40-100 kDa range and for the investigation of intermolecular interactions like protein-protein [79,89]; ligand-protein [88,90,91], DNA-protein [92] peptide-micelle [82,93,94] and peptide-protein [84]. Paramagnetic compounds such as TEMPOL and Gd(III)DTPA-BMA can be used to identify highly accessible regions of proteins [95].…”
Section: Paramagnetic Relaxationmentioning
confidence: 99%
“…From steady-state and equilibrium studies, the dissociation constant (k off ) for bPG is low, probably b50 s − 1 . 4,23 The paucity of information on the kinetics of bPG binding is due to difficulties in working with this unstable substrate (see, for example, Jakeman et al 26 ). Thus, Negelein found that at pH 7.2 and 38°C, bPG decomposed rapidly (half-life, 27 min).…”
Section: Introductionmentioning
confidence: 99%